PERFORMA PELAKSANAAN E-GOVERNMENT DALAM PELAYANAN ADMINISTRASI MASA PANDEMI COVID-19 DI NAGARI KOTO TANGAH BATU AMPA, AKABILURU, LIMA PULUH KOTA - Suryaningsih Suryaningsih; Rianda Prima Putri; Zamhasari Zamhasari; Tengku Fahrul Gafar (Ensiklopedia Sosial Review, 2022)
This study aims to see the performance of the implementation of e-Government in administrative services during the covid-19 pandemic in Nagari Koto Tangah Batu Ampa, Akabiluru district, Lima Puluh Kota regency. The background of this research is Nagari Koto Tangah Batu Ampa is one of the village in Akabiluru district that has implemented e-government in administrative services to the community during the covid-19 pandemic to date. The method used in this research is descriptive qualitative with case study type. This study uses the conceptmof Booz Allen and Hamilton to see the performance of government implementing e-government in term of five dimensions. That are benefits effeciency, participation, transparency, and change management. The result show that the implementation of e-government in Nagari Koto Tangah Batu Ampa is still not managed optimally bacause there are four dimensions that have not been optimally implemented (effeciency, participation, transparancy, and change management). The benefits of implementing e-government can already be felt by the nagari government and the community even though these four dimension have not run optimally.Keywords: Covid-19, e-government, village, service